Cardio-Protective Effect of Chickpea - Hayyan Hussain Hamza Alsulaymani , Mohammed Ibrahim Althawwabi , Ali Alwan Albardi , Mohammed Saeed alalawi , Mohammed Ali Barakat Alkinani , Wael Ali Mohammed Alshamrani; Sultan Abdullah Ibrahim Hassan , Mohammed Hussain Mobarak Aldowela , Ataa Saber Ataa AL Sulami , Mohammed Abdullah Ali Alzobaidi , Abdulaziz Jamaan Alomari , Fahad Saeed Althagafy (Migration Letters, 2022)
Chickpeas, an annual plant from the Fabaceae family, are abundant in protein, carbohydrates, fibre, essential minerals, and vitamins. It is grown all over the world and is considered an inexpensive and nutrient-dense pulse. Protein quality is better than in other pulses. Chickpea consumption is linked to better health outcomes. Chickpea protein peptides are becoming increasingly well recognised, and they can be formed by acid, alkaline, or enzymatic degradation. Enzymatic hydrolysis is considered safe, and various enzymes are used to synthesise peptides. These peptides have several bioactive properties, including angiotensin 1-converting enzyme inhibition, digestive sickness, hypocholesterolemia, cardiovascular disease, antioxidant activity, type 2 diabetes, anti-inflammatory, antibacterial, or anticarcinogenic activity. Diabetic rats reported significantly greater blood lipid profile values, including total cholesterol, triglycerides, LDL-C, and VLDL-C, despite a decrease in high-density lipoprotein. This might be due to increased free fatty acid release from insulin-resistant lipid cells, which are the primary cause of the fat changes associated with diabetic dyslipidemia. The higher lipid profile in the positive control group might be attributable to oxidative stress, which increases lipid peroxidation and reduces antioxidant defense capability.